EFFECTS OF DIETARY SUPPLEMENTATION OF YEAST (SACCHAROMYCES CEREVISIAE) CULTURE ON GROWTH PERFORMANCE, BLOOD PARAMETERS, NUTRIENT DIGESTIBILITY AND FECAL FLORA OF DAIRY HEIFERS - S. Ghazanfar; M. I. Anjum; A. Azim; I. Ahmed (Journal of Animal and Plant Sciences, 2015)
In a 120 day feeding trial, 8 cattle heifers (87±5 kg and 6 to 7 months) were randomly divided into two equal groups of four animals each (control and supplemented). During the trial, heifers in both the groups were offered National Research Council (NRC) recommended diet with or without yeast supplementation. The diet was formulated by adapting the small dairy breeds heifers’ nutrients requirements for growth rate of 0.6 kg/day considering body weight of 100 kg. The heifers in the supplemented group fed with Saccharomyces cerevisiae; Yea-Sac1026 (Alltech Inc., Nicholasville, KY), 5 g/animal/day. The effects of Saccharomyces cerevisiae on growth performance, blood parameters, nutrient digestibility, fecal coliform and Lactobacillus were studied. Average dry matter intake (DMI) was not different among both groups; whereas average daily weight gain was higher (p˂0.05) in supplemented compared with control group.The digestibility of dry matter, organic matter, crude protein, neuter detergent fibre and acid detergent fibre was higher (p˂0.05) in yeast-supplemented group compared with control group. Yeast-supplementation increased (p<0.05) the eosinophils and hemoglobin levels and erythrocytes and leukocytes counts.The average fecal population of Lactobacillus was greater (p˂0.05) with yeast-supplemented than in control group. It is therefore concluded that incorporation of Saccharomyces cerevisiae in the NRC recommended diet improved growth and health performance of dairy cattle heifers.
Keywords: Sahiwal heifers; Saccharomyces cerevisiae; Growth rate; Digestibility; Coliform; Lactobacillus